Research on simplified calculation method of aircraft flight load - SHI Hongwei; XUE Zihan; LUO Yang; CHEN Xiaorong (Hangkong gongcheng jinzhan, 2023)
Flight load analysis is a complex and arduous task, and developing a fast analysis method during the conceptual design stage is of great importance to improve the efficiency of flight load calculation. Based on the small disturbance linear analysis theory, the theoretical calculation methods of wing-body aerodynamic load, horizontal tail aerodynamic load, vertical tail aerodynamic load, control surface hinge moment, and the engineering calculation methods of aerodynamic load distribution, inertial load distribution, shear and bending moment of lift surface are summarized. This is a simplified calculation method of flight load. A mathematical model of a certain single seat competitive aircraft is established in the Matlab environment, taking the configuration dimension, mass characteristics and aerodynamic derivative as inputs, the response process of aerodynamic load, inertial load, control surface hinge moment, shear and bending moment are obtained. The results show that the simplified method can quickly get the dynamic parameters with less input data, and the calculation results can be used to satisfy the load requirements of structural design in the conceptual design stage.